Association between developmental defects of enamel and dental caries: A systematic review and meta-analysis. Issue 6 (June 2015) - Vargas-Ferreira, F.; Salas, M.M.S.; Nascimento, G.G.; Tarquinio, S.B.C.; Faggion, C.M.; Peres, M.A.; Thomson, W.M.; Demarco, F.F.
Abstract: Background: Dental caries is the main problem oral health and it is not well established in the literature if the enamel defects are a risk factor for its development. Objective: Studies have reported a potential association between developmental defects enamel (DDE) and dental caries occurrence. We investigated the association between DDE and caries in permanent dentition of children and teenagers. Data sources: A systematic review was carried out using four databases (Pubmed, Web of Science, Embase, and Science Direct), which were searched from their earliest records until December 31, 2014. Study selection: Population-based studies assessing differences in dental caries experience according to the presence of enamel defects (and their types) were included. PRISMA guidelines for reporting systematic reviews were followed. Meta-analysis was performed to assess the pooled effect, and meta-regression was carried out to identify heterogeneity sources. From the 2558 initially identified papers, nine studies fulfilled all inclusion criteria after checking the titles, abstracts, references, and complete reading. Seven of them were included in the meta-analysis with random model. Results: A positive association between enamel defects and dental caries was identified; meta-analysis showed that individuals with DDE had higher pooled odds of having dental caries experience [OR 2.21 (95% CI 1.3; 3.54)]. Meta-regression analysis demonstrated that adjustment for sociodemographic factors, countries' socioeconomic status, and bias (quality of studies) explained the high heterogeneity observed. Conclusion: A higher chance of dental caries should be expected among individuals with enamel defects.